Zabawka jako tekst kultury - Kajfosz, Jan (Studia Etnologiczne i Antropologiczne, 2011)
The article is devoted to the role of a toy in the process of getting to know the world by man in the process of enculturation. What constitutes the center of author’s attention is a toy programmed and made for children’s play, especially the toy, the aim of which is to represent something different — most often the thing which for man playing it, because of his/her low height, little experience and limited opportunities, is physically not available directly or often even dangerous (e.g. a dangerous car represented by a little car understood as its miniaturized model). A similar representation bases on the analogy, which allows for naming a given type of toy an iconic toy. It helps people to relatively safely get to know the world which is dangerous and difficult to grasp. The iconic toy in this sense serves to get familiarized with the world. Within the culture of a traditional type the iconicity of toy boils down to the analogy based on simplification. The culture toy of a traditional type is always distinguished by “essential” (in other words typical) object features it represents. Thus, it is somehow a counterpart of the prototype in the cognitivist theory in the sense that it is an idealized image of the thing represented. It is also its functional equivalent if one assumes that its task is to simplify and cognitively make available the world which, on account of its diversity and changeability, is cognitively intangible. Thus the aim of the traditional toy is to give the reality specific borders and accustom man to it, which is a condition of a cognitive ruling over the world. In the contemporary culture apart from iconic toys the analogy of which to the object they represent is based on simplification appear toys, the analogy of which to the represented object bases on “deformation” (e.g. an anthropomorphic monster with a non-standard number of eyes, limbs, etc.). From the cognitive point of view, similar toys do not confirm the world borders. On the contrary, they constantly disturb them, thus violating models, types and typologies. The function of similar toys in the enculturation process may lead to preparing man to functioning in the “fluid” modernity (Z. Bauman), which is characterized by instability of the cosmos borders in that that the very borders are prone to possible revisions and changes. Verbal play, developing in the situation of direct presence of the sender and receiver are extremely precious for retaining the identity of a child living in a multicultural environment. Spontaneous relations during play not only integrate the peer environment, but also give the sense of safety resulting from the belief that the remaining participants of the communication act have an analogical system of values, represent similar views and have a similar sense of aestheticism. A said word is the symbol of the living and dynamic culture which fulfills the needs of the group in a natural way. In the system of culture shaped in such a way foreign